2008
DOI: 10.1177/0092055x0803600303
|View full text |Cite
|
Sign up to set email alerts
|

The Face of Society

Abstract: We have updated Ferree and Hall's (1990) study of the way gender and race are constructed through pictures in introductory sociology textbooks. Ferree and Hall looked at 33 textbooks published between 1982 and 1988. We replicated their study by examining 3,085 illustrations in a sample of 27 textbooks, most of which were published between 2002 and 2006. We found important areas of progress in the presentation of both gender and race as well as significant areas of stasis. The face of society we found depicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the field of curriculum studies, textbook content analysis has been commonly used to examine the frequency and ways in which a variety of social groups are portrayed (Wade, 1993;Woyshner & Schocker, 2015). Curriculum scholars have found that information presented in textbooks often excludes or oversimplifies the experiences of marginalized social groups and contributes to perpetuating and reproducing the stereotypes and prejudices held by the dominant groups in the society (Avery & Simmons, 2000;Banks, 1969;Brown & Brown, 2010;Clark & Nunes, 2008;Field, Bauml, Wilhelm, & Jenkins, 2012;Journell, 2008;Suh et al, 2015;Woyshner & Schocker, 2015). For example, in his seminal study of the treatment of African Americans in 36 American history textbooks, Banks (1969) found that although textbooks did incorporate social problems related to African Americans, such as racism and discrimination, they failed to help students develop in-depth understandings of these issues.…”
Section: Textbook Representation Of Minority Groupsmentioning
confidence: 99%
“…In the field of curriculum studies, textbook content analysis has been commonly used to examine the frequency and ways in which a variety of social groups are portrayed (Wade, 1993;Woyshner & Schocker, 2015). Curriculum scholars have found that information presented in textbooks often excludes or oversimplifies the experiences of marginalized social groups and contributes to perpetuating and reproducing the stereotypes and prejudices held by the dominant groups in the society (Avery & Simmons, 2000;Banks, 1969;Brown & Brown, 2010;Clark & Nunes, 2008;Field, Bauml, Wilhelm, & Jenkins, 2012;Journell, 2008;Suh et al, 2015;Woyshner & Schocker, 2015). For example, in his seminal study of the treatment of African Americans in 36 American history textbooks, Banks (1969) found that although textbooks did incorporate social problems related to African Americans, such as racism and discrimination, they failed to help students develop in-depth understandings of these issues.…”
Section: Textbook Representation Of Minority Groupsmentioning
confidence: 99%
“…Little scholarship exists addressing settler colonialism in US introductory sociology textbooks. However, research addressing race and racism finds they often conservatively segregate these topics rather than theorizing them as structures holistically shaping all aspects of social life while idealizing racial integration through an uncritical lens of racial progress (Clark and Nunes, 2008; Ferree and Hall, 1996; Manza and Van Schyndel, 2000; Manza et al, 2010; Puentes and Gougherty, 2011; Seamster and Ray, 2018; Stone, 1996). Texts addressing Indigenous peoples erase or misname Indigenous communities, languages, culture, and history, and feature negative images reinforcing stereotypes of Indigenous people as pre-modern, uncivilized, and ‘other’ (Carroll, 2019; Steckley, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%